Preparation of murine submandibular salivary gland for upright intravital microscopy - Ficht, Xenia; Thelen, Flavian; Stolp-Rastätter, Bettina; Stein, Jens V. (JoVE. Video journal, 2018)
The submandibular salivary gland (SMG) is one of the three major salivary glands, and is of interest for many different fields of biological research, including cell biology, oncology, dentistry, and immunology. The SMG is an exocrine gland comprised of secretory epithelial cells, myofibroblasts, endothelial cells, nerves, and extracellular matrix. Dynamic cellular processes in the rat and mouse SMG have previously been imaged, mostly using inverted multi-photon microscope systems. Here, we describe a straightforward protocol for the surgical preparation and stabilization of the murine SMG in anesthetized mice for in vivo imaging with upright multi-photon microscope systems. We present representative intravital image sets of endogenous and adoptively transferred fluorescent cells, including the labeling of blood vessels or salivary ducts and second harmonic generation to visualize fibrillar collagen. In sum, our protocol allows for surgical preparation of mouse salivary glands in upright microscopy systems, which are commonly used for intravital imaging in the field of immunology.
Enthält auch eine Versuchsbeschreibung in Textform (8 Seiten)
Gesehen am 27.05.2020
Wissenschaftlicher Film. Schweiz. Deutschland. 2018
Keywords: Film